2021
DOI: 10.1093/rheumatology/keab542
|View full text |Cite
|
Sign up to set email alerts
|

A predictive clinical-radiomics nomogram for diagnosing of axial spondyloarthritis using MRI and clinical risk factors

Abstract: Objectives Construct and validate a nomogram model integrating the radiomics features and the clinical risk factors to differentiating axial spondyloarthritis (axSpA) in low back pain patients undergone sacroiliac joint (SIJ)- magnetic resonance imaging (MRI). Methods 638 patients confirmed as axSpA (n= 424) or non-axSpA (n = 214) who were randomly divided into training (n = 447) and validation cohorts (n = 191). Optimal radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…(2021), and Ye et al. (2022) have all shown strong positive evidence and low risk of bias during the early stages of development.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…(2021), and Ye et al. (2022) have all shown strong positive evidence and low risk of bias during the early stages of development.…”
Section: Resultsmentioning
confidence: 97%
“…Table 7 presents the RoB of identified studies ( n = 16) using the QUADAS‐2 tool. Five studies had a low overall RoB (Aghaei et al., 2015; Benditz et al., 2019, 2021; Kato et al., 2015; Roux et al., 2007; Ye et al., 2022) and nine studies demonstrated acceptable applicability (Aghaei et al., 2015; Benditz et al., 2019, 2021; Chatprem et al., 2021; Kato et al., 2009, 2015; Roux et al., 2007; Tominaga et al., 2022; Ye et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Radiomic analysis involving clinical factors and imaging demonstrates good clinical value in a variety of diseases (31)(32)(33)(34)(35). By extracting the high-throughput quantitative features from MRI scans, radiomics allows the non-invasive interpretation of tumor heterogeneity and biological characteristics (22,36).…”
Section: Discussionmentioning
confidence: 99%
“…Sacroiliitis is visually assessed on CT scans using gray scale descriptors, texture descriptors, which are effective prior features for mitigating the risk of over-fitting. As a result, radiomics has been applied extensively in the diagnosis of sacroiliitis (Faleiros 2018, Castro-Zunti et al 2020, Tenório et al 2020, Kepp et al 2021, Ye et al 2022. Ye et al (2022) improved the diagnostic accuracy from 74% to 78% using a model that combined the features of radiomics and clinical practice.…”
Section: And Radiomics Methodsmentioning
confidence: 99%